2021
DOI: 10.1016/s2213-2600(21)00310-6
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline for community treatment of suspected COVID-19 in people at high risk of adverse outcomes in the UK (PRINCIPLE): a randomised, controlled, open-label, adaptive platform trial

Abstract: Background Doxycycline is often used for treating COVID-19 respiratory symptoms in the community despite an absence of evidence from clinical trials to support its use. We aimed to assess the efficacy of doxycycline to treat suspected COVID-19 in the community among people at high risk of adverse outcomes. Methods We did a national, open-label, multi-arm, adaptive platform randomised trial of interventions against COVID-19 in older people (PRINCIPLE) across primary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 28 publications
2
55
2
Order By: Relevance
“…The SOC group with the largest number of patients ( 23 ) was used. Clinical results of the PRINCIPLE trial (ISRCTN86534580) were shown in three studies ( 28 30 ) comparing azithromycin, budesonide and doxycycline with SOC, respectively. Due to no overlap between the enrolment periods of the azithromycin and budesonide studies, we created a new SOC group by combining the two SOC groups and the PRINCIPLE trial was considered as a four-arm trial in the primary analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SOC group with the largest number of patients ( 23 ) was used. Clinical results of the PRINCIPLE trial (ISRCTN86534580) were shown in three studies ( 28 30 ) comparing azithromycin, budesonide and doxycycline with SOC, respectively. Due to no overlap between the enrolment periods of the azithromycin and budesonide studies, we created a new SOC group by combining the two SOC groups and the PRINCIPLE trial was considered as a four-arm trial in the primary analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Under the random-effects model, the estimated treatment effects relative to SOC were similar to those under the fixed-effects model but with wider credible intervals, e.g., tocilizumab with an OR of 0.91 (95% CrI [0.74,1.16]). In the sensitivity analysis by treating part A in the main randomization of RECOVERY ( 3 , 22 , 23 , 26 ), PRINCIPLE ( 28 30 ), REMAP-CAP ( 31 , 32 ), BLAZE-1 and two therapeutic-dose anticoagulation trials for critical and noncritical patients ( 36 , 37 ) as separated trials, all estimates were close to those in the primary analysis except for dexamethasone, which reported an OR of 0.97 (95% CrI [0.87,1.08]) in the primary analysis but 0.85 (95% CrI [0.76,0.95]) in the sensitivity analysis. The difference in the 28-day mortality rate between the SOC arm with the largest number of patients (22.4%, 1,162/5,181) and the SOC arm of the dexamethasone study ( 22 ) (25.7%, 1,110/4,321) mainly contributed to the discrepancy in the estimates of OR for dexamethasone vs. SOC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRINCIPLE trial has provided a robust in-pandemic trials platform. 2 , 3 , 13 The strength of this analysis is that the RSC has good data quality and is able to capture routine data about RTIs and their incidence. 14,15…”
Section: Discussionmentioning
confidence: 99%
“…The UK, primary care, prospective adaptive Platform Randomised trial of INterventions against COVID-19 In older peoPLE (PRINCIPLE) 1 has reported that two antibiotics, azithromycin and doxycycline, show no meaningful benefit in patient-reported recovery for coronavirus 2019 disease (COVID-19). 2 , 3 Azithromycin was included in PRINCIPLE between 23 May and 30 November 2020; doxycycline between 24 July and 14 December.…”
Section: Introductionmentioning
confidence: 99%